Research on Failure Mechanism and Strengthening of Broken Roadway Affected by Upper Coal Pillar. (1st April 2019) - He, Fulian; Zheng, Zheng; Zhu, Hengzhong; Yang, Bo
Abstract : The principal stress difference is introduced as a new evaluation index in order to better understand the failure mechanism of roadways affected by upper coal pillars and characterize failure of rock mass. Compared with traditional methods, it facilitates quantitative analysis. Moreover, we combine the semiplane theory and we obtain the stress distribution on the coal pillar's bedrock and the strengthening control area from the "change point" position along a 21 m horizontal line. The influence of multiple stresses induced from mining on a roadway is analyzed. It is found that rock failure is most likely while mining the 051606 working face, followed by mining the 051604 working face, and the stress influence on the upper pillar has the lowest failure probability. In addition, based on the asymmetry of the surrounding rock stress distribution, this study proposes strengthening control technology of surrounding rock on the basis of a highly stressed bolting support and anchor cable, adding to the steel ladder beam, steel mesh, and shed support's protective function to the roadway's roof and ribs. Finally, through field observations, it is concluded that the roadway deformation is within the controllable range.